2019
DOI: 10.1038/s41392-019-0086-1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive function and mechanism of HOXB13 in right-sided colon cancer

Abstract: Right-sided colon cancer (RCC) and left-sided colon cancer (LCC) differ in their clinical and molecular features. An investigation of differentially expressed genes (DEGs) between RCC and LCC could contribute to targeted therapy for colon cancer, especially RCC, which has a poor prognosis. Here, we identified HOXB13, which was significantly less expressed in RCC than in LCC and associated with prognosis in RCC, by using 5 datasets from the Gene Expression Omnibus (GEO). Tissue sample analysis showed that HOXB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…Homeobox B13 (HOXB13) is an important member of the HOX family, which encode nuclear transcription factors that drive cell differentiation during normal development and tumorigenesis ( 4 ). HOXB13 has been reported to act as a tumor suppressor gene in a number of types of human cancer, including colon cancer ( 5 ), prostate cancer ( 6 ) and renal cell carcinoma ( 7 ). A previous study demonstrated that HOXB13 expression was significantly downregulated in primary GC tissues compared with the corresponding non-malignant gastric tissues, and HOXB13 expression was positively correlated with the 5-year overall survival rate ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Homeobox B13 (HOXB13) is an important member of the HOX family, which encode nuclear transcription factors that drive cell differentiation during normal development and tumorigenesis ( 4 ). HOXB13 has been reported to act as a tumor suppressor gene in a number of types of human cancer, including colon cancer ( 5 ), prostate cancer ( 6 ) and renal cell carcinoma ( 7 ). A previous study demonstrated that HOXB13 expression was significantly downregulated in primary GC tissues compared with the corresponding non-malignant gastric tissues, and HOXB13 expression was positively correlated with the 5-year overall survival rate ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified HOXB13 as an upstream transcriptional regulator of HOXA11-AS in human bone metastatic prostate PC3 cells. Deregulation of HOXB13 expression has been implicated in a variety of other human cancers, functioning as a tumor-promoting factor in some tumor types and a tumor-repressing factor in other tumor types [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. Within the context of HOXB13-associated binding partners, HOXB13 may provide specificity for DNA binding and subsequent tumor progression or repression.…”
Section: Discussionmentioning
confidence: 99%
“…Given that canonical driver mutation genes such as APC , TP53 , and KRAS are shared by LCC and RCC, it is tempting to believe that activation of specific oncogenes and/or silencing of tumor suppressors may better explain their prognostic difference and also provide clues for treatment. Recently, HOXB13, another member of the homeobox gene family, was found to be downregulated in RCC via hypermethylation and to play a tumor suppressive role in RCC 20 . However, HOXC6 was confirmed to be overexpressed in RCC and associated with poor prognosis in this study, which is in line with previous studies in other cancer types 11 , 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%